AUDITORS’ EXPERIENCE, COMPETENCY, AND THEIR INDEPENDENCY AS THE INFLUENCIAL FACTORS IN PROFESSIONALISM - Gunasti Hudiwinarsih (Universitas Hayam Wuruk Perbanas, 2010)
The existence of auditor profession has been considered a primary factor. This is due to the importance of this profession in audit. In addition, the professional auditor can be more promisingly created. There are some factors influencing the auditors’ professional attitude so that it is urgent to do research on this matter. This research attempts to see the influence of experience, competency, and independency toward auditor professionalism, especially those who are under Public Accountant Office (KAP) in Surabaya. The analysis used in this re- search is a linear regression while the data were collected by distributing the questionnaires to the auditors under Public Accountant Office (KAP) in Surabaya. The research has forty one questionnaires and these are taken as the sample of research. The result of multiple regression shows that experience, competency, and independency influence significantly toward auditor professionalism. However, experience and independency have no effect sig- nificantly on their professionalism. On the contrary, competency influences significantly and positively toward the auditor professionalism.